Caracterização epidemiológica e espaço-temporal dos casos da leishmaniose tegumentar americana notificados no estado de Mato Grosso de 2011 a 2020 - Petroli, Steffany Weimer Santana (2024)
American Tegumentary Leishmaniasis (ATL) is a chronic, non-contagious disease considered a neglected zoonosis that affects the skin and mucous membranes, caused by different species of the Leishmania genus. Objective: To characterize the epidemiological profile and spatio-temporal distribution of American Tegumentary Leishmaniasis (ATL) and the factors associated with infection with the disease in the state of Mato Grosso, from 2011 to 2020. Method: This study was carried out in two stages, the first being a systematic review and meta-analysis of the prevalence of ATL in Brazil, and the second characterizing the epidemiological profile of ATL in the municipalities of the state of Mato Grosso. We considered studies that included patients with ATL diagnosed by at least one of the gold standard parasitological methods, PCR, or by serological methods (ELISA or IFI), excluding studies that analyzed cases confirmed as ATL using only one of the methods mentioned, not for diagnostic purposes, but to evaluate the effectiveness of treatments or other types of intervention. The second stage is an epidemiological study based on statistical data, during the period from 2011 to 2020, of the cases registered annually by the municipal health departments of the state of Mato Grosso and which are notified by the Information System for Diseases and Notification (SINAN). Results: Thirteen studies were included in the systematic review and meta-analysis. We found a combined prevalence in the general population of 40.0% (95% CI: 17.0-63.0%; weight 100%). When the prevalence was analyzed by state, we found a prevalence of 97.0% in Rio de Janeiro. The South and Southeast regions had the highest percentages, with 48.0%, followed by the Midwest region with 24.0%. In relation to the specific research on the state of Mato Grosso, between 2011 and 2020, 23,471 cases of ATL were reported, affecting mostly males, aged between 21 and 70 years, of brown race, with schooling from fifth to eighth grade incomplete. The cutaneous clinical form had a higher incidence than the mucosal form. The number of individuals living in urban and rural areas was similar. Among the municipalities in the state of Mato Grosso, Cuiabá (6.16%), Sinop (4.88%) and Barra do Garças (4.51%) accounted for most of the notifications. The areas with the highest rates are located in the municipalities belonging to the northern, northeastern and southwestern mesoregions of the state. Conclusion: Epidemiological changes, such as an increase in cases in urban areas, suggest progression in the transmission of ATL. Urbanization, deforestation, migration and inadequate housing conditions are factors that may contribute to this change. These findings could be valuable in guiding prevention and control strategies aimed at combating this neglected disease. The results found in the study are important both for the advancement of science and for public health. This understanding is essential to guide specific prevention and control strategies for the regions indicated, with the aim of effectively combating ATL and protecting the health of the affected populations.